A beam-type element for analyzing the eccentric load effect of box girder bridges. (February 2022) - Zhao, Chao; Zhou, Yi; Zhong, Xingu; Wang, Gang; Yang, Qunyu; Hu, Xiang
Abstract: Practical design of box girder bridges require the use of quick and simple calculation methods, rather than the complex numerical models based on shell or solid elements. In this paper, a beam-type element is proposed to analyze the eccentric load effect of box girder bridges, which is easily implemented in a computer program and efficient in computation. The element has two nodes, with four degrees of freedom (DOFs) per node, including two torsional DOFs and two distortional DOFs. To improve the accuracy of the beam-type element, the general solutions of the related governing differential equations are used to interpolate the torsional and distortional displacements within the element, and the coupling effect between torsion and distortion of the box girder bridge is ignored. The validity of the beam-type element is first verified by comparing numerical results with experimental data of a large scale model, and then it is applied to three real bridges to show why the proposed element is a good alternative to the traditional and time-consuming FE calculations.